2010
DOI: 10.1371/journal.pone.0013622
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Influenza with Hyperimmune Bovine Colostrum Antibody

Abstract: BackgroundDespite the availability of specific vaccines and antiviral drugs, influenza continues to impose a heavy toll on human health worldwide. Passive transfer of specific antibody (Ab) may provide a useful means of preventing or treating disease in unvaccinated individuals or those failing to adequately seroconvert, especially now that resistance to antiviral drugs is on the rise. However, preparation of appropriate Ab in large scale, quickly and on a yearly basis is viewed as a significant logistical hur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…Male BALB/c mice, 6 to 8 weeks old, were housed in specific-pathogen-free conditions at 21°C, 31% humidity. For each transmission experiment, two mice were infected to become the index mice, by either upper respiratory tract (URT) or total respiratory tract (TRT) routes, using direct delivery of the virus to the nares with a micropipette as described previously (33). After infection, index mice were housed separately for 6 h, unless otherwise stated, to prevent contamination of the contacts with the initial viral inoculum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male BALB/c mice, 6 to 8 weeks old, were housed in specific-pathogen-free conditions at 21°C, 31% humidity. For each transmission experiment, two mice were infected to become the index mice, by either upper respiratory tract (URT) or total respiratory tract (TRT) routes, using direct delivery of the virus to the nares with a micropipette as described previously (33). After infection, index mice were housed separately for 6 h, unless otherwise stated, to prevent contamination of the contacts with the initial viral inoculum.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were homogenized at 10,000 rpm for 30 s, and supernatants were clarified by centrifugation and stored at Ϫ80°C. Viral titers in secretions and tissues of the respiratory tract were determined by plaque assay on Madin-Darby canine kidney (MDCK) cells as previously described (33). Following 3 days of incubation, plaques were counted macroscopically to determine the PFU per sample, which was calculated from the average PFU obtained in three different dilutions of sample, each performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…BC-derived fractions rich in IgG have been successful in alleviating the symptoms of influenza in pretreated BALB/c mice [61]. These fractions were collected from cows immunized with A/Puerto Rico/8/34 (PR8) influenza virus, the IgG purified and delivered intranasally to mice.…”
Section: Viral and Bacterial Illnessesmentioning
confidence: 99%
“…It was demonstrated that the infection-induced inflammation that occurs in the digestive tract of HIV-infected individuals can be reversed with bovine colostrum [37]. The bovine colostrum could possibly improve the tissue repair, mucosal integrity and also have direct antimicrobial actions [38].…”
Section: Anti-hiv/aids Activity Of Bovine Colostrummentioning
confidence: 99%